An improved multiaxial stress-strain correction model for elastic FE postprocessing - Lang, Holger; Dreßler, Klaus (6th International Conference on Low Cycle Fatigue, 2008)
In this paper, the model of Köttgen, Barkey and Socie, which corrects the elastic stress and strain tensor histories at notches of a metallic specimen under non-proportional loading, is improved. It can be used in connection with any multiaxial σ-ε-law of incremental plasticity. For the correction model, we introduce a constraint for the strain components that goes back to the work of Hoffmann and Seeger. Parameter identification for the improved model is performed by Automatic Differentiation and an established least squares algorithm. The results agree accurately both with transient FE computations and notch strain measurements.
Keywords: Jiang’s Model of Elastoplasticity; Stress-strain correction; Parameter Identification; Automatic Differentiation; Least-Squares Optimization; Coleman-Li Algorithm